THE COMPETITIVENESS ANALYSIS OF COCOA COMMODITY IN THE DISTRICT OF SIGI - Andika Ibrahim; Marhawati Mappatoba; Yulianti Kalaba (AGROLAND: The Agricultural Sciences Journal, 2016)
This study aims to determine the competitiveness of cocoa commodity in the district of  Sigi and the impact of government policies by analyzing the effects of cocoa price changes, cocoa’s input price and cocoa production to the competitiveness of cocoa. Data collection is done in Sub-district of Palolo with the number of respondents 31 farmers and also data supported by data from other related agencies. The research objective answered by using analytical tools Policy Analysis Matrix (PAM). Results of the study found that cocoa in Sigi District has comparative and competitive advantages with the value of Domestic Cost Ratio (DCR) and the Private Cost Ratio (PCR) i.e. 0.45 and 0.50. Results for Nominal Protection coefficient of output value (NPCO) is 0.88 and Nominal Protection Coeffisients of Input (NPCI) is 0.80 respectively show the government's policies are protective for cocoa farmers in the district, while the EPC value is 0.89 indicates the policy is inhibiting the production of farmers with effect of ratio 0.09. The sensitivity analysis of changes in production, the price of cocoa bean and Subsidized- fertilizer prices, shows that the change in production is an indicator that most influence the competitiveness of cocoa in Sigi District.